The great transformation: The political and economic origins of our time - Polanyi, Karl; Stiglitz, Joseph E.; Block, Fred (Boston Beacon Press, 2025)
In this classic work of economic history and social theory, Karl Polanyi tracks the economic and social changes brought about by the "great transformation" of the Industrial Revolution. He pays particular attention to capitalism's rise and its role in fundamentally altering life after the Industrial Revolution. This seminal analysis explains not only the deficiencies of the self-regulating market, but the potentially dire social consequences of untempered market capitalism.